2022
DOI: 10.1177/21501319221088688
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Patient PPI Journey: Results of a Survey on PPI Treatment Initiation and Patient Experience

Abstract: Introduction: Proton pump inhibitors (PPIs) used in the management of gastro-esophageal reflux disease (GORD) are among the most frequently prescribed classes of drug worldwide. Currently, however, physicians are prescribing PPIs for extended periods, often without an indication, which is not in line with current guidance and therefore preventing appropriate reflux management. Inappropriate or excessive PPI prescribing is becoming increasingly visible, yet there is currently little research available on the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This pattern reflects a global demand in prescribing in this area and may be attributed to the effectiveness of the medication in managing gastro-oesophageal reflux disease, withdrawal of H2 receptor antagonists, an increasingly aging population, near patient testing for Helicobacter pylori and concomitant use of PPIs when prescribing drugs with gastrointestinal side effects. Conversely studies suggest that there is a mismatch between current PPI prescribing guidance and practice (Plehhova et al, 2022), indications for prescribing are poorly or not documented in up to 60% of cases (Patterson Burdsall et al, 2013) and clinicians and service users may be reluctant to stop treatment once initiated (Moriarty et al, 2016). Adverse events associated with inappropriate prescribing of PPIs such as antimicrobial resistance, electrolyte imbalance and increase risk of falls (Islama et al, 2018) suggest interventions to reduce inappropriate or unnecessary prescribing activity by prescribers in this area is a priority.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern reflects a global demand in prescribing in this area and may be attributed to the effectiveness of the medication in managing gastro-oesophageal reflux disease, withdrawal of H2 receptor antagonists, an increasingly aging population, near patient testing for Helicobacter pylori and concomitant use of PPIs when prescribing drugs with gastrointestinal side effects. Conversely studies suggest that there is a mismatch between current PPI prescribing guidance and practice (Plehhova et al, 2022), indications for prescribing are poorly or not documented in up to 60% of cases (Patterson Burdsall et al, 2013) and clinicians and service users may be reluctant to stop treatment once initiated (Moriarty et al, 2016). Adverse events associated with inappropriate prescribing of PPIs such as antimicrobial resistance, electrolyte imbalance and increase risk of falls (Islama et al, 2018) suggest interventions to reduce inappropriate or unnecessary prescribing activity by prescribers in this area is a priority.…”
Section: Discussionmentioning
confidence: 99%
“…HCPs are also often faced with a strong patient expectation for a pharmaceutical solution for their symptoms; indeed, in one study, physicians expressed the opinion that the ‘pressure to prescribe PPIs [as exerted by the patient] was outweighed by the pressure not to prescribe’ . 14 And yet, in another study, approximately half of patients reported concerns with being on a PPI in the long term, and a third indicated that they wanted to stop their PPI, 15 demonstrating a clear need for continued patient–physician communication beyond initial prescription. For those patients who go on to derive benefit from PPIs, the impetus to address dietary factors or consider other therapeutic options is removed so long as symptom relief is maintained.…”
Section: Factors Contributing To Ppi Overusementioning
confidence: 99%
“…14,15 In patients who fail to respond to PPI, poor adherence has been cited as the reason. 14 Furthermore, patient attitudes toward long-term PPI are mixed 45 and therefore additional treatments are warranted.…”
Section: Treatmentmentioning
confidence: 99%